2012
DOI: 10.1515/1935-1690.2166
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy Cyclicality and Growth within the US States

Abstract: We exploit differences in the stringency of balanced budget rules across US states to estimate the effect of fiscal policy cyclicality on state GDP growth. While most states have passed laws restricting deficits, the nature and strictness of these laws vary greatly. States with more stringent balanced budget restrictions run more procyclical fiscal policy. We use the diversity in these laws as an instrument for the cyclicality of state government spending. We find modest evidence that more counter-cyclical pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The strictness of balanced budget requirements exacerbates the procyclical behavior of state governments. States with stricter balance requirements are more likely to cut spending and raise taxes in response to unexpected deficits (Clemens and Miran, 2012; Svec and Kondo, 2012; Costello et al ., 2017), and states attempting to balance their budgets over a less-restrictive biennium rather than annually experience lower expenditure volatility (Kim and Wang, 2015).…”
Section: Us States and Balanced Budget Requirementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strictness of balanced budget requirements exacerbates the procyclical behavior of state governments. States with stricter balance requirements are more likely to cut spending and raise taxes in response to unexpected deficits (Clemens and Miran, 2012; Svec and Kondo, 2012; Costello et al ., 2017), and states attempting to balance their budgets over a less-restrictive biennium rather than annually experience lower expenditure volatility (Kim and Wang, 2015).…”
Section: Us States and Balanced Budget Requirementsmentioning
confidence: 99%
“…Spending increases at the subnational levels in the United States, in contrast, have been found to be associated with economic growth, with larger effects during recessionary periods (Atems, 2019) and lasting effects beyond the year in which the money is spent (Srithongrung and Kriz, 2014). Moreover, Svec and Kondo (2012) found that countercyclical deficit spending at the state level leads to larger growth rates, but states with stricter balanced budget requirements engage in more procyclical polices. Bi et al .…”
Section: Us States and Balanced Budget Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of additional lags does not change our results. Svec and Kondo (2012) estimate a regression specification that is similar to equation 2, but their study does not investigate the impact of fiscal policy on consumption or stock returns.…”
Section: State-level Fiscal Policymentioning
confidence: 99%